Yarravia oblongaLang & Cookson, 1935 emended, from the Lower Devonian of Victoria, Australia. Issue 3 (3rd July 2021) - McSweeney, Fearghus R.; Shimeta, Jeff; Buckeridge, John St. J. S.
Abstract: Yarravia oblonga is emended here and adds to our knowledge of floral diversity during the late Silurian and Early Devonian of central Victoria, Australia. Examination of specimens and analysis with light microscopy have revealed its defining characteristics as a slender elongate fructification, with most of the dichotomies in the fructification confined to the sterile axes. The sporangia of Y. oblonga are located centrally with sterile axes on the outside curving up and over the apices. The original diagnosis of a synangium is discounted as it was an artefact of preservation, and Hedeia is now considered a heterotypic synonym of Yarravia, with the latter taking priority. Furthermore, the branching pattern of Yarravia is simple and demonstrates that it does not belong with the 'trimerophyte grade'. The presence of Yarravia in South China is of palaeophytogeographical importance, as it suggests some exchange between the two regions or is evidence of convergent evolution. Fearghus R. McSweeney* [fearghus.mcsweeney@rmit.edu.au ] School of Science, RMIT University, Swanston Street, Melbourne 3000, Australia; Jeff Shimeta [jeff.shimeta@rmit.edu.au ] School of Science, RMIT University, Swanston Street, Melbourne 3000, Australia; John St. J. S. Buckeridge [john.buckeridge@rmit.edu.au ] Earth & Oceanic Systems Group, RMIT University, GPO Box 2476, Melbourne, Australia.